Read aloud handbook for Native American children - Waukau-Villagomez, Lauren; Villagomez, Samantha J. (Critical constructions., 2019)
This book is essential for teachers of reading and Native American Children to improve the reading scores of Native children. The book promotes the use of read alouds with Native American children in order to develop oral language, vocabulary and background knowledge. In addition, American Indian English and Standard English are discussed as issues for Native American Children. The importance of code-switching and bilingualism are examined so teacher have a better understanding of their students' worldviews. This will lead to a respect for the children's culture and subjugated knowledge.The book includes an annotated bibliography of books to use as read alouds. Many books have been field tested at Menominee Tribal School on school children in grades K-8. The books include some classic award-winning books and Native American books. The books were chosen for their use of Standard English. The Menominee Reservation is a focus of the book.